Antibacterial solvent-free coating and preparation method thereof

By adsorbing nanoscale zinc-carrying hydroxyapatite and cerium ammonium nitrate-modified nanoTiO2 composite antibacterial agents using microsphere carriers in solvent-free coatings, the problems of poor antibacterial performance and high VOC emissions of solvent-free coatings are solved, and the effects of efficient antibacterial and low VOC emissions are achieved.

CN119161798BActive Publication Date: 2025-03-14SICHUAN HAINA SYNERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411659753.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Existing solvent-free coatings lack antibacterial properties, resulting in the coating being susceptible to bacterial erosion, shortened service life, and high VOC emissions.

Method used

Microspheres are used as carriers to adsorb nanoscale zinc-carrying hydroxyapatite and cerium ammonium nitrate modified nanoTiO2 to form a complex antibacterial agent, combining physical destruction, charge action, reactive oxygen generation, inhibition of enzyme activity and interfering with gene expression.

Benefits of technology

The efficient antibacterial performance of the paint is achieved, with an antibacterial rate of more than 99.99%, while reducing VOC emissions and improving the stability and service life of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161798B_ABST
    Figure CN119161798B_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial solvent-free coating and a preparation method thereof, belonging to the field of coatings. The antibacterial solvent-free coating comprises component A and component B; component A comprises the following components in parts by weight: 45-70 parts of vegetable oil-based modified polyol, 0.5-1.5 parts of antibacterial agent, 20-40 parts of pigments and fillers, and 4-8 parts of film-forming aids; component B is a silane-modified terminal isocyanate prepolymer; the mass ratio of component A to component B is (2-2.4):1; the antibacterial agent in component A is a composite antibacterial agent, and the composite antibacterial agent comprises nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface; the mass ratio of nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and the intermediate carrier is 3:2:5. The coating of the invention has excellent antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of coatings and relates to an antibacterial solvent-free coating and a preparation method thereof. Background Art

[0002] Based on the dispersion medium, commonly used coatings currently include oil-based, water-based, and solvent-free coatings. While oil-based coatings offer mature processes and excellent film quality, their primary drawbacks are a strong odor and extremely high and persistent VOC emissions. While water-based coatings are relatively environmentally friendly and have low VOC emissions, they offer inferior film quality and are highly dependent on the environment and equipment. Therefore, the development of solvent-free coatings has become a key area of ​​coatings R&D.

[0003] At present, most solvent-free coatings prepared do not have antibacterial properties or have poor antibacterial properties. The coatings cannot resist the erosion of bacteria or microorganisms for a long time. The corrosion phenomenon in the coatings will gradually intensify. As the microorganisms continue to multiply, the pollution and degradation of the coating surface will become more and more serious, and even the coating film may peel or fall off, which will eventually shorten the service life of the coating. Summary of the Invention

[0004] The purpose of the present invention is to provide an antibacterial solvent-free coating and a preparation method thereof, which solves the problem that there is currently no solvent-free coating with good antibacterial properties and low VOC emissions.

[0005] The technical solution adopted in the present invention is as follows:

[0006] An antibacterial solvent-free coating, comprising component A and component B;

[0007] The component A comprises the following components in parts by weight: 45-70 parts of vegetable oil-based modified polyol, 0.5-1.5 parts of antibacterial agent, 20-40 parts of pigment and filler, and 4-8 parts of film-forming aid;

[0008] The component B is a silane-modified isocyanate-terminated prepolymer;

[0009] The mass ratio of component A to component B is (2~2.4):1;

[0010] The antibacterial agent in component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent;

[0011] The mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and intermediate carrier is 3:2:5;

[0012] The surface porosity of the microspheres is 30%-60%, the particle size D90 of the microspheres is 10-15 μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 is 50-80 nm, and the pore size of the microsphere surface is 50-100 nm.

[0013] In the present invention, the surface porosity of the microspheres is 30%-60%, which refers to the distribution width of the surface porosity of all microspheres participating in the reaction. The distribution width of 30%-60% means that a large number of microspheres participating in the reaction have a surface porosity of 30%, 40%, 50%, 60%, or all of the above.

[0014] In the present invention, the particle size D90 of the microspheres is 10-15 μm, which means that 90% of all the microspheres participating in the reaction have a particle size of 10-15 μm. Similarly, the particle size D90 of the nano-scale zinc-loaded hydroxyapatite and the nano-TiO2 modified by ammonium cerium nitrate is 50-80 nm, which means that 90% of all the nano-scale zinc-loaded hydroxyapatite and the nano-TiO2 modified by ammonium cerium nitrate participating in the reaction have a particle size of 50-80 nm. The pore size of the microsphere surface is 50-100 nm, which means that the particle size distribution of the pores on the surface of a single microsphere is within a width range of 50-100 nm.

[0015] In the present invention, component B is a curing agent for component A. Components A and B are uniformly mixed to obtain an antibacterial coating. After mixing components A and B, a cross-linking curing reaction occurs. The main reaction mechanism that imparts properties to the paint film is:

[0016] —N=C=O + HO - = —NH—COO - ;

[0017] Hydroxyapatite is a carrier of zinc ions, which can cause bacterial death or abnormal growth through physical destruction, charge effects, or by promoting the generation of reactive oxygen species, inhibiting enzyme activity, and interfering with gene expression. The specific explanation is:

[0018] Physical destruction: The high specific surface area of ​​nanoparticles enables them to directly contact the bacterial cell membrane and destroy its structure, leading to bacterial death.

[0019] Charge effect: Zinc ions can bind to negatively charged molecules on bacterial cell membranes through electrostatic attraction, interfering with cell membrane function and affecting the normal physiological activities of bacteria.

[0020] Reactive oxygen generation: Zinc particles can catalyze the production of highly oxidizing reactive oxygen species, which can destroy the cell structure of bacteria and cause bacterial death.

[0021] Inhibit enzyme activity: Zinc ions can bind to various enzymes in bacteria, inhibit their activity, and block the normal growth and metabolic pathways of bacteria.

[0022] Interference with gene expression: Zinc ions can interfere with gene expression by affecting bacterial DNA replication and transcription, thereby inhibiting bacterial growth.

[0023] Nano-TiO2 is a photocatalytic semiconductor material. When irradiated by ultraviolet light, the valence electrons will be excited to the conduction band, thereby generating highly active photogenerated electron-hole pairs. These pairs have strong redox properties and can destroy the cell structure of bacteria, leading to bacterial death.

[0024] The antibacterial agent prepared by loading zinc ions on hydroxyapatite has the antibacterial effect of metal ions, and nano-TiO2 has a photocatalytic antibacterial effect. The composite antibacterial agent of the present invention organically combines the photocatalytic decomposition of bacteria and the antibacterial effect of metal ions, and exhibits ultra-efficient antibacterial performance both indoors and outdoors.

[0025] In addition, the present invention uses microspheres as carriers to adsorb nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate on their surfaces to form a composite antibacterial material, thereby avoiding the dispersion of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate separately in the coating. Since nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate have different antibacterial properties, if nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are independently dispersed in the coating, some parts of the coating will not have nano-TiO2 modified by ammonium cerium nitrate or nano-scale zinc-loaded hydroxyapatite, which will adversely affect the antibacterial properties of the coating.

[0026] Therefore, the present invention uses microspheres as carriers, and the minimum unit of the composite antibacterial material formed by the simultaneous adsorption of nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 on the microspheres is a microsphere surface on which nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 are simultaneously adsorbed. The microspheres are uniformly dispersed in the coating under the action of a dispersant. After the microspheres are uniformly dispersed in the coating, basically every part of the coating formed has the dual antibacterial properties of nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2; in the present invention, the adsorption amount of nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 by a single microsphere has little effect on the antibacterial effect, because multiple microspheres are distributed on the coating, and the synergistic effect of multiple microspheres can achieve a better antibacterial effect on the corresponding parts.

[0027] The addition of ammonium cerium nitrate in the present invention inhibits the growth of nano-TiO2 grains, so that the grain size is kept smaller. The smaller grain size means a higher specific surface area and more surface atoms, thereby improving the efficiency of the photocatalytic reaction. This is because more surface atoms can provide more reaction sites, making it easier for photogenerated electrons and holes to react with surrounding oxygen and water molecules to generate more active oxygen species; therefore, the ammonium cerium nitrate-modified nano-TiO2 enhances the antibacterial properties of TiO2.

[0028] The antibacterial coating of the present invention has the advantages of broad-spectrum antibacterial properties, excellent antibacterial performance, and long-lasting and stable antibacterial effect. According to the test requirements of GB / T 21866-2008 standard, the antibacterial rate of the antibacterial coating prepared by the present invention is greater than 99.99%. The solvent-free antibacterial coating of the present invention can be stably stored for more than 6 months. The coating has excellent stability and high antibacterial properties.

[0029] Furthermore, the composite antibacterial agent is prepared by the following method:

[0030] S1. Preparation of intermediate carrier

[0031] S1.1. Preparation of solid microspheres: dissolving polylactic acid-polymethyl methacrylate block copolymer and polyethylene glycol in dichloromethane, stirring evenly, then adding calcium sulfate and stirring evenly to obtain a polymer solution; slowly adding the polymer solution dropwise to an aqueous phase containing polyvinyl alcohol, and emulsifying the solution using an ultrasonic emulsifier at room temperature to form a stable O / W emulsion; placing the O / W emulsion at 30-40°C to evaporate the solvent; after the solvent is completely evaporated, separating the microspheres from the emulsion using a centrifuge, washing the microspheres with deionized water multiple times, and drying to obtain solid microspheres;

[0032] S1.2, Surface Pore Formation: Immerse the solid microspheres in a phosphoric acid etchant and etch at 25°C for 30-40 minutes. Wash and dry to obtain solid microspheres with pores distributed on the surface.

[0033] S1.3. Surface modification of microspheres: first, 3-(acryloyloxy)propyltrimethoxysilane is prepared into a silane coupling agent solution with a mass fraction of 1.2%, and then solid microspheres with pores distributed on the surface are immersed in the silane coupling agent solution. After keeping for 2 hours, the microspheres are taken out and dried at 60°C for 1 hour to obtain microspheres modified with the silane coupling agent; then, a photosensitive compound is dissolved in chloroform to obtain a photosensitive compound solution, and then the silane coupling agent-modified microspheres are immersed in the photosensitive compound solution, reacted at room temperature for 7-8 hours, and then filtered and dried to obtain solid microspheres with pores distributed on the surface after surface modification with 3-(acryloyloxy)propyltrimethoxysilane and the photosensitive compound, wherein the surface-modified solid microspheres with pores distributed on the surface are intermediate carriers; wherein, the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system;

[0034] S2, preparing nano-scale zinc-loaded hydroxyapatite;

[0035] S3, preparing ammonium cerium nitrate modified nano-TiO2;

[0036] S4. Place nano-TiO2 modified by ammonium cerium nitrate and nano-zinc-loaded hydroxyapatite in anhydrous ethanol solution, disperse them by ultrasonication to form a uniform suspension, then add the intermediate carrier into the suspension, stir continuously at 30°C for 10-12 hours, filter and dry to obtain microspheres with nano-zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate adsorbed on the surface, which is a composite antibacterial agent.

[0037] The present invention uses polylactic acid-polymethyl methacrylate block copolymer as a raw material for preparing microspheres, and utilizes the good biocompatibility and excellent temperature resistance of the polylactic acid-polymethyl methacrylate block copolymer. Because the curing reaction of the coating component A and component B in the present invention is an exothermic reaction, in order to avoid the adverse effect of the temperature increase of the curing reaction on the stability of the microspheres, the present invention selects polylactic acid-polymethyl methacrylate block copolymer with good temperature resistance as the raw material for preparing microspheres; polyethylene glycol and calcium sulfate are added in the process of preparing microspheres. Polyethylene glycol and calcium sulfate are pore inhibitors that can reduce the porosity inside the microspheres. The internal porosity of the solid microspheres finally obtained is very low; due to the adsorption of nitric acid by the microspheres If there are too many pores inside the nano-TiO2 modified by ammonium cerium and the nano-zinc-loaded hydroxyapatite, the nano-TiO2 modified by ammonium cerium nitrate and the nano-zinc-loaded hydroxyapatite will enter the interior of the microspheres, and the microspheres will hinder the response of the nano-TiO2 modified by ammonium cerium nitrate to light, thereby adversely affecting the photocatalytic reaction thereof; the microspheres will hinder the release of zinc ions in the nano-zinc-loaded hydroxyapatite and its contact with bacteria; therefore, the present invention prepares solid microspheres with small internal porosity; then, pores are formed on the surface of the microspheres, so that the nano-TiO2 modified by ammonium cerium nitrate and the nano-zinc-loaded hydroxyapatite are adsorbed on the surface of the microspheres, thereby reducing the influence of the microspheres on the antibacterial properties of the nano-TiO2 modified by ammonium cerium nitrate and the nano-zinc-loaded hydroxyapatite.

[0038] The present invention adopts 3-(acryloyloxy)propyltrimethoxysilane to modify the interface of the microspheres, thereby strengthening the adsorption firmness of the ammonium cerium nitrate modified nano-TiO2, nano-scale zinc-loaded hydroxyapatite and the microspheres; the present invention also adopts a photosensitive compound to modify the surface of the microspheres, which is equivalent to adding a photosensitive compound to the carrier of the ammonium cerium nitrate modified nano-TiO2. When the photosensitive compound is exposed to light, it transfers the absorbed light energy to the ammonium cerium nitrate modified nano-TiO2, thereby stimulating more electron transitions in the ammonium cerium nitrate modified nano-TiO2, thereby increasing the number of photogenerated electrons and holes on the surface of titanium dioxide, thereby improving its ability to generate free radicals, and making the ammonium cerium nitrate modified nano-TiO2 have better antibacterial properties.

[0039] Furthermore, the amount of polyethylene glycol added is 5% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, the amount of calcium sulfate added is 1% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, and the concentration of polyvinyl alcohol is 0.5 wt %.

[0040] Furthermore, the phosphoric acid etchant is composed of the following components in mass fractions: 25% phosphoric acid, 58% citric acid, 1% surfactant, and the balance being deionized water.

[0041] Furthermore, the preparation method of the nano-scale zinc-loaded hydroxyapatite is: preparing hydroxy titanium phosphate by coprecipitation reaction with calcium nitrate, disodium hydrogen phosphate and titanium sulfate, and then preparing the nano-scale zinc-loaded hydroxy titanium phosphate by ion exchange method with zinc ions.

[0042] Furthermore, the ammonium cerium nitrate modified nano-TiO2 is prepared by the following method: adding appropriate amounts of anhydrous ethanol, hydrochloric acid and butyl titanate to a three-necked flask, and ultrasonically dispersing for 30 minutes to form a titanium source solution; dissolving the ammonium cerium nitrate in ethanol and stirring evenly to obtain a modifier solution; under stirring conditions, slowly adding the modifier solution dropwise to the titanium source solution, mixing and stirring at a speed of 500-800 r / min for 2-4 hours to obtain a transparent sol; after drying and grinding the transparent sol, calcining at 800°C for 5 hours in a nitrogen atmosphere to obtain the ammonium cerium nitrate modified nano-TiO2.

[0043] Furthermore, the component B is prepared by the following method: adding a vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stirring at 90-120°C for 1-2 hours, and then transferring it to a reactor equipped with a vacuum device, increasing the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, maintaining it at 180-220°C for 2-3 hours, cooling it to room temperature, and then transferring it back to the four-necked flask; then, under the protection of dry nitrogen, stirring, slowly adding isophorone diisocyanate, an organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine to the four-necked flask, raising the temperature to 60-90°C after the addition is complete, maintaining it for 2-3 hours, and then cooling it to room temperature to obtain a silane-modified terminal isocyanate prepolymer.

[0044] Furthermore, the pigments and fillers in component A include the following components in parts by weight: 15 to 25 parts of titanium dioxide with a particle size of 800 mesh, 5 to 15 parts of talc with a particle size of 3000 mesh, and 5 to 15 parts of heavy calcium carbonate with a particle size of 1250 mesh;

[0045] The film-forming aid comprises the following components in parts by weight: 0.2-0.4 parts of an organosilicon defoamer, 1-2 parts of a wetting and leveling agent, 1-2.5 parts of a dispersant, 2-3.5 parts of a retarder, and 1.5-3 parts of an adhesion promoter;

[0046] The component A is prepared by the following method: placing a vegetable oil-based modified polyol and a dispersant in a high-speed disperser, mechanically stirring for 5-10 minutes at a speed of 500-700 r / min, then slowly adding an organic defoamer dropwise to the mixture, continuing to stir and mix in the high-speed disperser for 10 minutes, then sequentially adding an antibacterial agent, titanium dioxide, talc, and heavy calcium to the disperser, mechanically stirring for 50-90 minutes at a speed of 1200-1500 r / min, wherein the slurry temperature does not exceed 60° C. during the stirring process, then adding a wetting and leveling agent, a retarder, and an adhesion enhancer, mechanically stirring for 10-30 minutes at a speed of 500-700 r / min to obtain a crude product, and then filtering the crude product through a 150-mesh gauze and packaging it to obtain component A.

[0047] Furthermore, an antibacterial solvent-free coating comprises component A and component B;

[0048] The component A comprises the following components in parts by weight: 70 parts of vegetable oil-based modified polyol, 1.5 parts of antibacterial agent, 40 parts of pigment and filler, and 8 parts of film-forming aid;

[0049] The component B is a silane-modified terminal isocyanate prepolymer; the mass ratio of component A to component B is 2.2:1;

[0050] The antibacterial agent in component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; the mass ratio of nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and the intermediate carrier is 3:2:5; the surface porosity of the microsphere is 30%-60%, the particle size D90 of the microsphere is 10-15 μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are both 50-80 nm, and the pore size of the pores on the surface of the microsphere is 50-100 nm;

[0051] The film-forming aid comprises the following components in parts by weight: 0.3 parts of organosilicon defoamer, 1.5 parts of wetting and leveling agent, 1.5 parts of dispersant, 2.5 parts of retarder, and 2 parts of adhesion promoter;

[0052] The pigments and fillers in component A include the following components in parts by weight: 20 parts of titanium dioxide with a particle size of 800 mesh, 10 parts of talc with a particle size of 3000 mesh, and 10 parts of heavy calcium carbonate with a particle size of 1250 mesh.

[0053] A method for preparing an antibacterial solvent-free coating comprises the following steps:

[0054] A. Synthesis of component A: Place the vegetable oil-based modified polyol and dispersant in a high-speed disperser, mechanically stir for 5-10 minutes at a speed of 500-700 r / min, then slowly add the organic defoamer dropwise to the mixture, continue stirring and mixing in the high-speed disperser for 10 minutes, then add the antibacterial agent, titanium dioxide, talc, and heavy calcium carbonate to the disperser in sequence, mechanically stir for 50-90 minutes at a speed of 1200-1500 r / min, and keep the slurry temperature below 60°C during the stirring process, then add the wetting and leveling agent, retarder, and adhesion enhancer, mechanically stir for 10-30 minutes at a speed of 500-700 r / min to obtain a crude product, and then filter the crude product through a 150-mesh gauze and package it to obtain component A;

[0055] B. Synthesis of component B: Add a vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stir at 90-120°C for 1-2 hours, transfer the mixture to a reactor equipped with a vacuum pump, increase the vacuum at a rate of -0.02 MPa / h to a degree of -0.08 to -0.12 MPa, maintain the temperature at 180-220°C for 2-3 hours, cool the mixture to room temperature, and then transfer the mixture back to the four-necked flask; then, under the protection of dry nitrogen, slowly add isophorone diisocyanate, an organobismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine dropwise to the four-necked flask with stirring. After the addition is complete, raise the temperature to 60-90°C, maintain the temperature for 2-3 hours, then cool the temperature to room temperature and discharge the mixture to obtain a silane-modified terminal isocyanate prepolymer.

[0056] C. Component A and component B are uniformly mixed to obtain an antibacterial solvent-free coating.

[0057] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0058] 1. The present invention employs microspheres as carriers for an antibacterial solvent-free coating. Microspheres are simultaneously adsorbed onto nano-sized zinc-loaded hydroxyapatite and ammonium cerium nitrate-modified nano-TiO2 to form a composite antibacterial material. The microspheres are uniformly dispersed throughout the coating, resulting in a coating that exhibits the dual antibacterial properties of nano-sized zinc-loaded hydroxyapatite and ammonium cerium nitrate-modified nano-TiO2 on virtually every surface.

[0059] 2. The present invention prepares solid microspheres with low internal porosity; pores are then created on the surface of the microspheres, allowing the ammonium cerium nitrate-modified nano-TiO2 and nano-scale zinc-loaded hydroxyapatite to adsorb on the surface of the microspheres, thereby reducing the impact of the microspheres on the antibacterial properties of the ammonium cerium nitrate-modified nano-TiO2 and nano-scale zinc-loaded hydroxyapatite.

[0060] 3. The present invention uses polylactic acid-polymethyl methacrylate block copolymer as the raw material for preparing microspheres, utilizing the good biocompatibility and excellent temperature resistance of polylactic acid-polymethyl methacrylate block copolymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be considered as limiting the scope. A person of ordinary skill in the art can also derive other relevant drawings based on these drawings without inventive effort, among which:

[0062] Figure 1 is a SEM scanning electron microscope image of the solid microspheres in Example 1 of the present invention;

[0063] Figure 2 is a cross-sectional SEM image of the solid microspheres in Example 1 of the present invention;

[0064] Figure 3 This is a SEM image of the solid microspheres with pores distributed on the surface after pore formation in Example 1 of the present invention;

[0065] Figure 4 is a cross-sectional SEM scanning electron microscope image of the solid microspheres prepared in Comparative Example 12 of the present invention;

[0066] Figure 5 This is a cross-sectional SEM image of a solid microsphere with pores distributed on its surface after pore formation in Example 1 of the present invention;

[0067] Figure 6 This is a SEM scanning electron microscope image of the surface of the microspheres of the composite antibacterial agent in Example 1 of the present invention. DETAILED DESCRIPTION

[0068] In order to make the objectives, technical solutions, and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only intended to explain the present invention and are not intended to limit the present invention. That is, the embodiments described herein are only some embodiments of the present invention, not all embodiments. Generally, the components of the embodiments of the present invention described and illustrated in the drawings herein may be arranged and designed in various different configurations.

[0069] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention as claimed, but is merely intended to represent selected embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative work are within the scope of protection of the present invention.

[0070] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus comprising the element.

[0071] The features and performance of the present invention are further described in detail below with reference to the embodiments.

[0072] An antibacterial solvent-free coating, comprising component A and component B;

[0073] The component A comprises the following components in parts by weight: 45-70 parts of a vegetable oil-based modified polyol, 0.5-1.5 parts of an antimicrobial agent, 20-40 parts of a pigment or filler, and 4-8 parts of a film-forming aid; the vegetable oil-based modified polyol is a vegetable oil-based modified polyol having a functionality of 2 or 3 and a relative molecular weight of less than 2000, such as Vantellus D2000 modified castor oil polyol or Puranol D210 vegetable oil-based modified polyol;

[0074] The component B is a silane-modified isocyanate-terminated prepolymer;

[0075] The mass ratio of component A to component B is (2~2.4):1;

[0076] The antibacterial agent in component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent;

[0077] The mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and intermediate carrier is 3:2:5;

[0078] The surface porosity of the microspheres is 30%-60%, the particle size D90 of the microspheres is 10-15 μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 is 50-80 nm, and the pore size of the microsphere surface is 50-100 nm.

[0079] The composite antibacterial agent is prepared by the following method:

[0080] S1. Preparation of intermediate carrier

[0081] S1.1. Preparation of solid microspheres: dissolving polylactic acid-polymethyl methacrylate block copolymer and polyethylene glycol in dichloromethane, stirring evenly, then adding calcium sulfate and stirring evenly to obtain a polymer solution; slowly adding the polymer solution dropwise to an aqueous phase containing polyvinyl alcohol, and emulsifying the solution using an ultrasonic emulsifier at room temperature to form a stable O / W emulsion; placing the O / W emulsion at 30-40°C to evaporate the solvent; after the solvent is completely evaporated, separating the microspheres from the emulsion using a centrifuge, washing the microspheres with deionized water multiple times, and drying to obtain solid microspheres;

[0082] S1.2. Surface pore formation: solid microspheres are immersed in a phosphoric acid etchant, etched at 25°C for 30 minutes, and washed and dried to obtain solid microspheres with pores distributed on the surface; the porosity of the microsphere surface after etching with the etchant of the present invention can reach 30-60%. A porosity higher than 30% has a good adsorption effect, and a porosity exceeding 60% is difficult to achieve because, when the surface porosity exceeds 60%, the interior of the microsphere will be etched to a certain extent.

[0083] S1.3. Surface modification of microspheres: first, 3-(acryloyloxy)propyltrimethoxysilane is prepared into a silane coupling agent solution with a mass fraction of 1.2%, and then solid microspheres with pores distributed on the surface are immersed in the silane coupling agent solution. After keeping for 2 hours, the microspheres are taken out and dried at 60°C for 1 hour to obtain microspheres modified with the silane coupling agent; then, a photosensitive compound is dissolved in chloroform to obtain a photosensitive compound solution, and then the silane coupling agent-modified microspheres are immersed in the photosensitive compound solution, reacted at room temperature for 7-8 hours, and then filtered and dried to obtain solid microspheres with pores distributed on the surface after surface modification with 3-(acryloyloxy)propyltrimethoxysilane and the photosensitive compound, wherein the surface-modified solid microspheres with pores distributed on the surface are intermediate carriers; wherein, the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system;

[0084] S2, preparing nano-scale zinc-loaded hydroxyapatite;

[0085] S3, preparing ammonium cerium nitrate modified nano-TiO2;

[0086] S4. Place nano-TiO2 modified by ammonium cerium nitrate and nano-zinc-loaded hydroxyapatite in anhydrous ethanol solution, disperse them by ultrasonication to form a uniform suspension, then add the intermediate carrier into the suspension, stir continuously at 30°C for 10-12 hours, filter and dry to obtain microspheres with nano-zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate adsorbed on the surface, which is a composite antibacterial agent.

[0087] The amount of polyethylene glycol added is 5% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, the amount of calcium sulfate added is 1% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, and the concentration of polyvinyl alcohol is 0.5wt%.

[0088] The phosphoric acid etchant is composed of the following components by mass fraction: 25% phosphoric acid, 58% citric acid, 1% surfactant, and the balance deionized water. The phosphoric acid etchant is prepared by sequentially adding weighed phosphoric acid and citric acid to a mixing container, adding deionized water, and stirring thoroughly with a stirring device until the phosphoric acid and citric acid are completely dissolved. The surfactant is then added and stirred until completely dispersed to obtain the phosphoric acid etchant. The surfactant can be sodium dodecyl sulfonate.

[0089] The nano-sized zinc-loaded hydroxyapatite is prepared by coprecipitating calcium nitrate, disodium hydrogen phosphate, and titanium sulfate to produce titanium hydroxyphosphate, followed by ion exchange between zinc ions and titanium hydroxyphosphate. Nano-sized zinc-loaded hydroxyapatite is known in the art, as is the preparation method.

[0090] The ammonium cerium nitrate modified nano-TiO2 is prepared by the following method: adding appropriate amounts of anhydrous ethanol, hydrochloric acid and butyl titanate into a three-necked flask, and ultrasonically dispersing for 30 minutes to form a titanium source solution; dissolving the ammonium cerium nitrate in ethanol and stirring evenly to obtain a modifier solution; under stirring conditions, slowly adding the modifier solution dropwise to the titanium source solution, mixing and stirring at a speed of 500-800 r / min for 2-4 hours to obtain a transparent sol; after drying and grinding the transparent sol, calcining at 800°C for 5 hours in a nitrogen atmosphere to obtain the ammonium cerium nitrate modified nano-TiO2.

[0091] The component B is prepared by the following method: adding a vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stirring at 90-120° C. for 1-2 hours, and then transferring it to a reactor equipped with a vacuum device, increasing the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, maintaining the temperature at 180-220° C. for 2-3 hours, cooling to room temperature, and then transferring it back to the four-necked flask; then, under the protection of dry nitrogen, slowly adding isophorone diisocyanate, an organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine dropwise to the four-necked flask with stirring; after the addition is complete, heating to 60-90° C., maintaining the temperature for 2-3 hours, and then cooling to room temperature for discharging to obtain a silane-modified terminal isocyanate prepolymer. The vegetable oil-based modified polyol used to prepare component B and the vegetable oil-based modified polyol in component A may be the same substance.

[0092] The pigments and fillers in component A include the following components in parts by weight: 15-25 parts of titanium dioxide with a particle size of 800 mesh, 5-15 parts of talc with a particle size of 3000 mesh, and 5-15 parts of heavy calcium carbonate with a particle size of 1250 mesh;

[0093] The film-forming aid comprises the following components in parts by weight: 0.2-0.4 parts of an organosilicon defoamer, 1-2 parts of a wetting and leveling agent, 1-2.5 parts of a dispersant, 2-3.5 parts of a retarder, and 1.5-3 parts of an adhesion promoter; wherein the organosilicon defoamer may be a polydimethylsiloxane-based organosilicon defoamer, the wetting and leveling agent may be DHX-104E, DHX-04, or LW-604, the dispersant may be DISPERBYK-2008 or DISPERBYK-110, etc., the retarder may be citric acid, tartaric acid, or sodium methyl tartrate, etc., and the adhesion promoter may be PEAP 1600 or PEAP 1611;

[0094] The component A is prepared by the following method: placing a vegetable oil-based modified polyol and a dispersant in a high-speed disperser, mechanically stirring for 5-10 minutes at a speed of 500-700 r / min, then slowly adding an organic defoamer dropwise to the mixture, continuing to stir and mix in the high-speed disperser for 10 minutes, then sequentially adding an antibacterial agent, titanium dioxide, talc, and heavy calcium to the disperser, mechanically stirring for 50-90 minutes at a speed of 1200-1500 r / min, wherein the slurry temperature does not exceed 60° C. during the stirring process, then adding a wetting and leveling agent, a retarder, and an adhesion enhancer, mechanically stirring for 10-30 minutes at a speed of 500-700 r / min to obtain a crude product, and then filtering the crude product through a 150-mesh gauze and packaging it to obtain component A.

[0095] Preferably, an antibacterial solvent-free coating comprises component A and component B;

[0096] The component A comprises the following components in parts by weight: 70 parts of vegetable oil-based modified polyol, 1.5 parts of antibacterial agent, 40 parts of pigment and filler, and 8 parts of film-forming aid;

[0097] The component B is a silane-modified terminal isocyanate prepolymer; the mass ratio of component A to component B is 2.2:1;

[0098] The antibacterial agent in component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; the mass ratio of nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and the intermediate carrier is 3:2:5; the surface porosity of the microsphere is 30%-60%, the particle size D90 of the microsphere is 10-15 μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are both 50-80 nm, and the pore size of the pores on the surface of the microsphere is 50-100 nm;

[0099] The film-forming aid comprises the following components in parts by weight: 0.3 parts of organosilicon defoamer, 1.5 parts of wetting and leveling agent, 1.5 parts of dispersant, 2.5 parts of retarder, and 2 parts of adhesion promoter;

[0100] The pigments and fillers in component A include the following components in parts by weight: 20 parts of titanium dioxide with a particle size of 800 mesh, 10 parts of talc with a particle size of 3000 mesh, and 10 parts of heavy calcium carbonate with a particle size of 1250 mesh.

[0101] A method for preparing an antibacterial solvent-free coating comprises the following steps:

[0102] A. Synthesis of component A: Place the vegetable oil-based modified polyol and dispersant in a high-speed disperser, mechanically stir for 5-10 minutes at a speed of 500-700 r / min, then slowly add the organic defoamer dropwise to the mixture, continue stirring and mixing in the high-speed disperser for 10 minutes, then add the antibacterial agent, titanium dioxide, talc, and heavy calcium carbonate to the disperser in sequence, mechanically stir for 50-90 minutes at a speed of 1200-1500 r / min, and keep the slurry temperature below 60°C during the stirring process, then add the wetting and leveling agent, retarder, and adhesion enhancer, mechanically stir for 10-30 minutes at a speed of 500-700 r / min to obtain a crude product, and then filter the crude product through a 150-mesh gauze and package it to obtain component A;

[0103] B. Synthesis of component B: Add a vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stir at 90-120°C for 1-2 hours, and then transfer to a reactor equipped with a vacuum pump. The vacuum is increased at a rate of -0.02 MPa / h to a degree of vacuum of -0.08 to -0.12 MPa. The temperature is maintained at 180-220°C for 2-3 hours, cooled to room temperature, and then transferred back to the four-necked flask. Subsequently, isophorone diisocyanate, an organobismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine are slowly added dropwise to the four-necked flask under the protection of dry nitrogen. After the addition is complete, the temperature is raised to 60-90°C, maintained for 2-3 hours, and then cooled to room temperature to obtain a silane-modified terminal isocyanate prepolymer. The organobismuth metal catalyst can be tributyl bismuth, triisopropyl bismuth, or bismuth isooctanoate.

[0104] C. Component A and component B are uniformly mixed to obtain an antibacterial solvent-free coating.

[0105] Example 1

[0106] A preferred embodiment of the present invention provides an antibacterial solvent-free coating, comprising component A and component B;

[0107] The component A comprises the following components in parts by weight: 70 parts of vegetable oil-based modified polyol, 1.5 parts of antibacterial agent, 40 parts of pigment and filler, and 8 parts of film-forming aid; wherein the vegetable oil-based modified polyol is Vantellus D2000 modified castor oil polyol, and the vegetable oil-based plasticizer is acetyl tributyl citrate;

[0108] The component B is a silane-modified terminal isocyanate prepolymer; the mass ratio of component A to component B is 2.2:1;

[0109] The antibacterial agent in component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; the mass ratio of nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and the intermediate carrier is 3:2:5; the surface porosity of the microsphere is 30%-60%, the particle size D90 of the microsphere is 10-15 μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are both 50-80 nm, and the pore size of the pores on the surface of the microsphere is 50-100 nm;

[0110] The preparation method of the composite antibacterial agent is:

[0111] S1. Preparation of intermediate carrier

[0112] S1.1. Preparation of solid microspheres: dissolve polylactic acid-polymethyl methacrylate block copolymer and polyethylene glycol in dichloromethane, stir well, then add calcium sulfate, stir well to obtain a polymer solution; slowly add the polymer solution dropwise to the aqueous phase containing polyvinyl alcohol, and emulsify it with an ultrasonic emulsifier at room temperature to form a stable O / W emulsion; place the O / W emulsion at 30-40°C to evaporate the solvent, and when the solvent is completely evaporated, separate the microspheres from the emulsion by a centrifuge, wash the microspheres with deionized water several times, and then dry to obtain solid microspheres; the amount of polyethylene glycol added is 5% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, the amount of calcium sulfate added is 1% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, and the concentration of polyvinyl alcohol is 0.5wt%;

[0113] The SEM scanning electron microscope image of the solid microspheres is as follows Figure 1 As shown, the cross-sectional SEM scanning electron microscope image of the solid microsphere is as follows Figure 2 shown; combined Figure 1 、 Figure 2 As shown, the solid microspheres in the present invention are solid microsphere structures with low internal porosity;

[0114] S1.2. Surface pore formation: The solid microspheres were immersed in a phosphoric acid etchant and etched at 25°C for 40 minutes. After washing and drying, the solid microspheres were obtained. The phosphoric acid etchant was composed of the following components by weight: 25% phosphoric acid, 58% citric acid, 1% surfactant, and the balance deionized water.

[0115] The SEM scanning electron microscope image of solid microspheres with pores distributed on the surface is as follows Figure 3 As shown, the surface of the obtained microspheres has voids; the cross-sectional SEM scanning electron microscope image of the solid microspheres with pores on the surface is shown in Figure 5 As shown. Figure 2 and Figure 5 It can be seen that the pores inside the microspheres did not change significantly after etching, indicating that no etching occurred inside the microspheres.

[0116] S1.3. Surface modification of microspheres: first, 3-(acryloyloxy)propyltrimethoxysilane is prepared into a silane coupling agent solution with a mass fraction of 1.2%, and then solid microspheres with pores distributed on the surface are immersed in the silane coupling agent solution. After keeping for 2 hours, the microspheres are taken out and dried at 60°C for 1 hour to obtain microspheres modified with the silane coupling agent; then, a photosensitive compound is dissolved in chloroform to obtain a photosensitive compound solution, and then the silane coupling agent-modified microspheres are immersed in the photosensitive compound solution, reacted at room temperature for 7-8 hours, and then filtered and dried to obtain solid microspheres with pores distributed on the surface after surface modification with 3-(acryloyloxy)propyltrimethoxysilane and the photosensitive compound, wherein the surface-modified solid microspheres with pores distributed on the surface are intermediate carriers; wherein, the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system;

[0117] S2. Preparation of nano-scale zinc-loaded hydroxyapatite: Calcium nitrate, disodium hydrogen phosphate, and titanium sulfate are used to prepare titanium hydroxyphosphate by coprecipitation reaction, the prepared titanium hydroxyphosphate is dispersed in deionized water to form a suspension, and zinc sulfate solution is slowly added dropwise to the suspension to allow zinc ions to undergo an ion exchange reaction with calcium ions in the titanium hydroxyphosphate to prepare nano-scale zinc-loaded hydroxyapatite. This method is prior art and the detailed steps are not described here.

[0118] S3. Preparation of ammonium cerium nitrate modified nano-TiO2: Add appropriate amounts of anhydrous ethanol, hydrochloric acid and butyl titanate to a three-necked flask, and ultrasonically disperse for 30 minutes to form a titanium source solution; dissolve ammonium cerium nitrate in ethanol and stir evenly to obtain a modifier solution; under stirring conditions, slowly add the modifier solution dropwise to the titanium source solution, mix and stir at a speed of 500-800 r / min for 2-4 hours to obtain a transparent sol; after drying and grinding the transparent sol, calcinate at 800°C under a nitrogen atmosphere for 5 hours to obtain ammonium cerium nitrate modified nano-TiO2;

[0119] S4. Place nano-TiO2 modified by ammonium cerium nitrate and nano-zinc-loaded hydroxyapatite in anhydrous ethanol solution, disperse them ultrasonically to form a uniform suspension, then add the intermediate carrier to the suspension, stir continuously at 30°C for 10-12 hours, filter and dry to obtain microspheres with nano-zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate adsorbed on the surface, which is the composite antibacterial agent; the SEM scanning electron microscope image of the microsphere surface of the composite antibacterial agent is as follows: Figure 6 As shown, there are obvious particles adhering to the surface;

[0120] The film-forming aid includes the following components in parts by weight: 0.3 parts of an organosilicon defoamer, 1.5 parts of a wetting and leveling agent, 1.5 parts of a dispersant, 2.5 parts of a retarder, and 2 parts of an adhesion promoter; the organosilicon defoamer is a polydimethylsiloxane-based organosilicon defoamer, the wetting and leveling agent is DHX-104E, the dispersant is DISPERBYK-2008 dispersant, the retarder is citric acid, and the adhesion promoter is PEAP 1600.

[0121] The pigments and fillers in component A include the following components in parts by weight: 20 parts of titanium dioxide with a particle size of 800 mesh, 10 parts of talc with a particle size of 3000 mesh, and 10 parts of heavy calcium carbonate with a particle size of 1250 mesh.

[0122] A method for preparing an antibacterial solvent-free coating comprises the following steps:

[0123] A. Synthesis of component A: Place the vegetable oil-based modified polyol and dispersant in a high-speed disperser and mechanically stir for 5 minutes at a speed of 700 r / min. Then, slowly add the organic defoamer dropwise to the mixture and continue stirring and mixing in the high-speed disperser for 10 minutes. Then, add the antibacterial agent, titanium dioxide, talc, and heavy calcium carbonate to the disperser in sequence and mechanically stir for 50 minutes at a speed of 1500 r / min. During the stirring process, the slurry temperature is 50°C. Then, add the wetting and leveling agent, retarder, and adhesion enhancer and mechanically stir for 10 minutes at a speed of 700 r / min to obtain a crude product. Then, filter the crude product through a 150-mesh gauze and package it to obtain component A.

[0124] B. Synthesis of component B: Add a vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stir at 110°C for 1.5 hours, and then transfer to a reactor equipped with a vacuum pump. Increase the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, maintain at 200°C for 3 hours, cool to room temperature, and then transfer back to the four-necked flask; then, under the protection of dry nitrogen, slowly add isophorone diisocyanate, an organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine dropwise to the four-necked flask with stirring. After the addition is complete, raise the temperature to 80°C, maintain for 3 hours, and then cool to room temperature to obtain a silane-modified terminal isocyanate prepolymer; wherein the organic bismuth metal catalyst is tributyl;

[0125] C. Component A and component B are uniformly mixed to obtain an antibacterial solvent-free coating.

[0126] The VOC emission of the coating prepared in this embodiment is less than 20 g / L (national standard 100 g / L, GB30981-2020).

[0127] Example 2

[0128] This example is based on Example 1, differing from Example 1 in that the mass ratio of component A to component B is 2:1. All other aspects are the same as Example 1. The coating prepared in this example has a VOC emission of less than 20 g / L (national standard: 100 g / L, GB30981-2020).

[0129] Example 3

[0130] This example is based on Example 1, differing from Example 1 in that the mass ratio of component A to component B is 2.4:1. All other aspects are the same as Example 1. The coating prepared in this example has a VOC emission of less than 20 g / L (national standard: 100 g / L, GB30981-2020).

[0131] Example 4

[0132] This embodiment is based on Example 1, and differs from Example 1 in that component A in this embodiment includes the following components in parts by weight: 45 parts of vegetable oil-based modified polyol, 0.5 parts of antibacterial agent, 20 parts of pigment and filler, and 4 parts of film-forming aid;

[0133] The pigments and fillers in component A include the following components in parts by weight: 15 parts of titanium dioxide with a particle size of 800 mesh, 5 parts of talc with a particle size of 3000 mesh, and 5 parts of heavy calcium carbonate with a particle size of 1250 mesh;

[0134] The film-forming aid comprises the following components in parts by weight: 0.2 parts of organosilicon defoamer, 1 part of wetting and leveling agent, 1 part of dispersant, 2 parts of retarder, and 1.5 parts of adhesion promoter;

[0135] The component A is prepared by the following method: placing a vegetable oil-based modified polyol and a dispersant in a high-speed disperser, mechanically stirring for 10 minutes at a speed of 500 r / min, then slowly adding an organic defoamer dropwise to the mixture, continuing to stir and mix in the high-speed disperser for 10 minutes, then sequentially adding an antibacterial agent, titanium dioxide, talc, and heavy calcium to the disperser, mechanically stirring for 90 minutes at a speed of 1200 r / min, the slurry temperature being 50° C. during the stirring process, then adding a wetting and leveling agent, a retarder, and an adhesion enhancer, mechanically stirring for 30 minutes at a speed of 500 r / min to obtain a crude product, and then filtering the crude product through a 150-mesh gauze and packaging to obtain component A.

[0136] The rest are the same as in Example 1. The VOC emission of the coating prepared in this example is less than 20 g / L (national standard 100 g / L, GB30981-2020).

[0137] Example 5

[0138] This embodiment is based on Example 1, and differs from Example 1 in that component A in this embodiment includes the following components in parts by weight: 62.5 parts of vegetable oil-based modified polyol, 1 part of antibacterial agent, 30 parts of pigments and fillers, and 6 parts of film-forming aids;

[0139] The pigments and fillers in component A include the following components in parts by weight: 25 parts of titanium dioxide with a particle size of 800 mesh, 15 parts of talc with a particle size of 3000 mesh, and 15 parts of heavy calcium carbonate with a particle size of 1250 mesh;

[0140] The film-forming aid comprises the following components in parts by weight: 0.4 parts of organosilicon defoamer, 2 parts of wetting and leveling agent, 2.5 parts of dispersant, 3.5 parts of retarder, and 3 parts of adhesion promoter;

[0141] Component A is prepared by the following method: placing a vegetable oil-based modified polyol, a vegetable oil-based plasticizer, and a dispersant in a high-speed disperser and mechanically stirring for 8 minutes at a speed of 600 r / min. Then, an organic defoamer is slowly added dropwise to the mixture, and stirring and mixing in the high-speed disperser for 10 minutes. Then, an antibacterial agent, titanium dioxide, talc, and heavy calcium carbonate are sequentially added to the disperser and mechanically stirred for 70 minutes at a speed of 1300 r / min. During the stirring process, the slurry temperature is maintained at 50°C. Then, a wetting and leveling agent, a retarder, and an adhesion enhancer are added, and mechanical stirring is performed for 20 minutes at a speed of 600 r / min to obtain a crude product. The crude product is then filtered through a 150-mesh gauze and packaged to obtain component A. The coating prepared in this example has a VOC emission of less than 20 g / L (national standard 100 g / L, GB30981-2020).

[0142] Comparative Example 1

[0143] This comparative example is based on Example 1, but differs from Example 1 in that the mass ratio of component A to component B in this comparative example is 1.8:1. The rest of the ingredients are the same as those in Example 1.

[0144] Comparative Example 2

[0145] This comparative example is based on Example 1, but differs from Example 1 in that the mass ratio of component A to component B in this comparative example is 2.5:1. The rest of the ingredients are the same as those in Example 1.

[0146] Comparative Example 3

[0147] This comparative example is based on Example 1, but differs from Example 1 in that no intermediate carrier is added to the composite antibacterial agent of this comparative example, and no intermediate carrier (microspheres) need to be prepared. The preparation method of the composite antibacterial agent in this comparative example is as follows: nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate-modified nano-TiO2 in a mass ratio of 3:2 are weighed and placed in an anhydrous ethanol solution, and after ultrasonic dispersion, the composite antibacterial agent of this comparative example is obtained by repeatedly washing with deionized water and ethanol.

[0148] Comparative Example 4

[0149] This comparative example is based on Example 1, but differs from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2, and the intermediate carrier in the composite antibacterial agent of this comparative example is 2:2:5.

[0150] Comparative Example 5

[0151] This comparative example is based on Example 1, but differs from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2, and the intermediate carrier in the composite antibacterial agent of this comparative example is 1:2:5.

[0152] Comparative Example 6

[0153] This comparative example is based on Example 1, but differs from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2, and the intermediate carrier in the composite antibacterial agent of this comparative example is 3:2:4.

[0154] Comparative Example 7

[0155] This comparative example is based on Example 1, but differs from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2, and the intermediate carrier in the composite antibacterial agent of this comparative example is 3:2:6.

[0156] Comparative Example 8

[0157] This comparative example is based on Example 1, but differs from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2, and the intermediate carrier in the composite antibacterial agent of this comparative example is 4:2:5.

[0158] Comparative Example 9

[0159] This comparative example is based on Example 1, but different from Example 1 in that 3-(acryloyloxy)propyltrimethoxysilane is not used to modify the surface of the microspheres in the composite antibacterial agent of this comparative example, and only a photosensitive compound is used to modify the surface of the microspheres, and the steps are: dissolving the photosensitive compound in chloroform to obtain a photosensitizing compound solution, then immersing the microspheres in the photosensitive compound solution, reacting at room temperature for 7-8 hours, and then filtering and drying to obtain solid microspheres with pores distributed on the surface after surface modification by the photosensitive compound, wherein the solid microspheres with pores distributed on the surface after surface modification are intermediate carriers; wherein the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system.

[0160] Comparative Example 10

[0161] This comparative example is based on Example 1, but different from Example 1 in that the composite antibacterial agent of this comparative example does not use a photosensitive compound to modify the microspheres, but only uses 3-(acryloyloxy)propyltrimethoxysilane for modification. The specific steps are: 3-(acryloyloxy)propyltrimethoxysilane is configured as a silane coupling agent solution with a mass fraction of 1.2%, and then solid microspheres with pores distributed on the surface are immersed in the silane coupling agent solution. After keeping for 2 hours, the microspheres are taken out and dried at 60°C for 1 hour to obtain microspheres modified with the silane coupling agent.

[0162] Comparative Example 11

[0163] This comparative example is based on Example 1, but differs from Example 1 in that the composite antibacterial agent of this comparative example does not use photosensitizing compounds and 3-(acryloyloxy)propyltrimethoxysilane to modify the surface of the microspheres.

[0164] Comparative Example 12

[0165] This comparative example is based on Example 1, and the difference from Example 1 is that polyethylene glycol and calcium sulfate are not added in the composite antibacterial agent of this comparative example during the preparation of microspheres. The cross-sectional SEM scanning electron microscope image of the solid microspheres prepared in this comparative example is as follows: Figure 4 As shown, compared Figure 2 and Figure 4 It can be seen that without the addition of polyethylene glycol and calcium sulfate, there are a large number of voids inside the microspheres. The presence of a large number of voids inside the microspheres will affect the antibacterial performance of the coating.

[0166] Test Example 1

[0167] According to the requirements of GB / T 21866-2008, the antibacterial rates of the antibacterial coatings prepared in Examples 1-5 and Comparative Examples 1-12 were tested. Nano-zinc-loaded hydroxyapatite targets common bacteria, such as Escherichia coli and Staphylococcus aureus, while nano-TiO2 modified with ammonium cerium nitrate primarily produces free radicals through photocatalysis, which requires illumination during use. Therefore, in this test example, the antibacterial rates of the antibacterial coatings prepared in Examples 1-5 and Comparative Examples 1-12 were measured under both illumination and non-illumination conditions, in accordance with GB / T 21866-2008. The antibacterial rate under illumination was 1, while the antibacterial rate under non-illumination was 2. The results are shown in Table 1.

[0168] Test method: Bacterial species: Staphylococcus aureus; Control sample: Coating test plate without antibacterial component added (solvent-free coating prepared according to the ratio and preparation method of Example 1 without adding antibacterial component); Antibacterial coating test sample: Coating test plate of antibacterial coating prepared in Examples 1-5 and Comparative Examples 1-12; Bacteria were evenly inoculated on the test sample using a quantitative inoculation method, and after inoculation, covered with a sterilized cover film to ensure uniform contact of the bacteria with the sample; Placed in a constant temperature incubator for 24 hours, culture conditions were 37°C, relative humidity was 90%, and cultured under two lighting conditions, with and without light (according to the above method, carried out under the conditions of no light and with light, fluorescent light can be used); After removing the sample, rinse thoroughly with eluent, dilute and count the viable bacteria by pouring method, and calculate the inhibition rate based on the number of viable bacteria;

[0169] Inhibition rate = (number of colonies in the control sample - number of colonies in the experimental sample) / number of colonies in the control sample × 100%;

[0170] Control sample colony count: refers to the colony count obtained by counting viable bacteria after inoculation of a sample plate that has not been treated with antimicrobial agents (i.e., control sample) for a certain period of time (e.g., 24 hours);

[0171] Colony count of experimental sample: refers to the colony count obtained under the same inoculation and culture conditions of the sample plate that has been treated with antibacterial agents (i.e., experimental sample); Level I requirement is ≥99.00%, and Level II requirement is ≥90.00% (less than 99.00%); for example, if the number of viable bacteria after inoculation of the blank control sample is 10,000 cfu (colony forming units) / plate, and the number of viable bacteria after inoculation of the antibacterial sample is 100 cfu / plate, the antibacterial rate is calculated as follows: Antibacterial rate = (10,000 - 100) / 10,000 × 100% = 99%, which meets the requirements of Level I products.

[0172]

[0173] During testing, the same batch of coatings may correspond to multiple coating test panels. Therefore, the greater the difference between the maximum and minimum antibacterial rates, the more uneven the distribution of antibacterial performance. In Examples 1-5, the maximum difference in antibacterial rate between illuminated and dark conditions was 0.003%, a very small difference, indicating a relatively uniform distribution of antibacterial performance. Combined with the data in Table 1, Example 1 of the present invention is the optimal preparation method. The resulting solvent-free antibacterial coating exhibits excellent antibacterial performance and a uniform distribution of antibacterial performance. Furthermore, the solvent-free antibacterial coating prepared in Example 1 has a VOC emission level of less than 20 g / L (national standard: 100 g / L, GB30981-2020), a coating with abrasion resistance six times that of the national standard (national standard ≤ 0.03 g, this product ≤ 0.005 g, GB / T22374-2018), and a combustion performance that meets the non-flammable A (A2-s1, t0) grade (GB8624-2012).

[0174] Test Example 2

[0175] The antibacterial coatings prepared in Example 1 and Comparative Example 3 were used as experimental samples. According to the detection method of Test Example 1, 30 identical coating test plates were prepared from the antibacterial coating prepared in Example 1. Similarly, 30 identical coating test plates were prepared from the antibacterial coating prepared in Comparative Example 3. The above 60 coating test plates were placed in a constant temperature incubator for 24 hours under the incubation conditions of 37°C, 90% relative humidity, and light. The antibacterial rates of the 60 coating test plates were calculated according to Test Example 1. The maximum antibacterial rate and the minimum antibacterial rate of the 30 antibacterial coating test plates corresponding to Example 1 were then calculated. The difference in the maximum antibacterial rate is recorded as the first difference; at the same time, the difference between the maximum antibacterial rate and the minimum antibacterial rate in the 30 antibacterial coating test plates corresponding to Comparative Example 3 is calculated and recorded as the second difference; the first difference is 0.001%, and the second difference is 1.13%; the greater the difference between the maximum antibacterial rate and the minimum antibacterial rate in the antibacterial coating test plates of the same coating, the more uneven the antibacterial distribution of the coating; therefore, the uniformity of the antibacterial property of the coating prepared in Example 1 of the present invention is higher than that of the coating prepared in Comparative Example 3; it shows that the antibacterial property of the composite antibacterial agent with the addition of an intermediate carrier is more uniform.

[0176] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An antibacterial solvent-free coating, characterized in that: Comprising component A and component B; The component A comprises the following components in parts by weight: 45-70 parts of vegetable oil-based modified polyol, 0.5-1.5 parts of antibacterial agent, 20-40 parts of pigment and filler, and 4-8 parts of film-forming aid; The component B is a silane-modified terminal isocyanate prepolymer; The mass ratio of component A to component B is (2~2.4):1; The antibacterial agent in component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; The mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and the intermediate carrier is 3:2:5; The surface porosity of the microspheres is 30%-60%, the particle size D90 of the microspheres is 10-15 μm, the particle size D90 of the nano-scale zinc-loaded hydroxyapatite and the ammonium cerium nitrate modified nano-TiO2 is 50-80 nm, and the pore size of the surface pores of the microspheres is 50-100 nm; The composite antibacterial agent is prepared by the following method: S1. Preparation of intermediate carrier S1.1, preparation of solid microspheres: polylactic acid-polymethyl methacrylate block copolymer and polyethylene glycol are dissolved in dichloromethane, and calcium sulfate is added after stirring evenly, and stirred evenly to obtain a polymer solution; the polymer solution is slowly added dropwise to the aqueous phase containing polyvinyl alcohol, and emulsified by ultrasonic emulsifier at room temperature to form a stable O / W type emulsion; the O / W type emulsion is placed at 30-40°C to volatilize the solvent, and when the solvent is completely volatilized, the microspheres are separated from the emulsion by a centrifuge, the microspheres are washed with deionized water for multiple times, and then dried to obtain solid microspheres; S1.2, surface pore formation: soak the solid microspheres in phosphoric acid etchant, etch at 25°C for 30-40 minutes, wash and dry to obtain solid microspheres with pores distributed on the surface; S1.3, microsphere surface modification: firstly prepare 3-(acryloxy)propyltrimethoxysilane into a silane coupling agent solution with a mass fraction of 1.2%, then immerse the solid microspheres with pores on the surface into the silane coupling agent solution, keep for 2 hours, take out the microspheres and dry them at 60°C for 1 hour to obtain microspheres modified by the silane coupling agent; The photosensitive compound is dissolved in chloroform to obtain a photosensitive compound solution, and then the microspheres modified with a silane coupling agent are immersed in the photosensitive compound solution, reacted at room temperature for 7-8 hours, filtered and dried to obtain solid microspheres with pores on the surface after surface modification by 3-(acryloyloxy)propyltrimethoxysilane and the photosensitive compound, and the solid microspheres with pores on the surface after surface modification are intermediate carriers; wherein the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system; S2, preparing nano-scale zinc-loaded hydroxyapatite; S3, preparing ammonium cerium nitrate modified nano-TiO2; S4. Place nano-TiO2 modified by ammonium cerium nitrate and nano-zinc-loaded hydroxyapatite in anhydrous ethanol solution, disperse by ultrasonication to form a uniform suspension, add the intermediate carrier into the suspension, stir continuously for 10-12 hours at 30°C, filter and dry to obtain microspheres with nano-zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate adsorbed on the surface, which is the composite antibacterial agent.

2. The antibacterial solvent-free coating according to claim 1, characterized in that: The amount of polyethylene glycol added is 5% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, the amount of calcium sulfate added is 1% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, and the concentration of polyvinyl alcohol is 0.5wt%.

3. The antibacterial solvent-free coating according to claim 1, characterized in that: The phosphoric acid etchant is composed of the following components in mass fractions: 25% phosphoric acid, 58% citric acid, 1% surfactant, and the balance is deionized water.

4. The antibacterial solvent-free coating according to claim 1, characterized in that: The preparation method of the nano-scale zinc-loaded hydroxyapatite is as follows: calcium nitrate, disodium hydrogen phosphate and titanium sulfate are used to prepare hydroxy titanium phosphate through a coprecipitation reaction, and then zinc ions and hydroxy titanium phosphate are used to prepare the nano-scale zinc-loaded hydroxy titanium apatite through an ion exchange method.

5. The antibacterial solvent-free coating according to claim 1, characterized in that: The ammonium cerium nitrate modified nano-TiO2 is prepared by the following method: adding appropriate amounts of anhydrous ethanol, hydrochloric acid and butyl titanate into a three-necked flask, and then ultrasonically dispersing for 30 minutes to form a titanium source solution; Dissolve ammonium cerium nitrate in ethanol and stir evenly to obtain a modifier solution; Under stirring conditions, the modifier solution is slowly added to the titanium source solution, and the mixture is stirred at a speed of 500-800 r / min for 2-4 hours to obtain a transparent sol. After the transparent sol is dried and ground, it is calcined at 800°C for 5 hours in a nitrogen atmosphere to obtain ammonium cerium nitrate modified nano-TiO2.

6. The antibacterial solvent-free coating according to claim 1, characterized in that: The component B is prepared by the following method: adding a vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stirring at 90-120° C. for 1-2 h, then transferring to a reactor equipped with a vacuum pump, increasing the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, maintaining at 180-220° C. for 2-3 h, cooling to room temperature, and then transferring back to the four-necked flask; subsequently, stirring under the protection of dry nitrogen, slowly dropping isophorone diisocyanate, an organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine into the four-necked flask, raising the temperature to 60 to 90° C. after the addition is complete, maintaining for 2-3 h, then cooling to room temperature, and discharging to obtain a silane-modified terminal isocyanate prepolymer.

7. The antibacterial solvent-free coating according to claim 1, characterized in that: The pigment filler in component A includes the following components in parts by weight: 15-25 parts of titanium dioxide with a particle size of 800 mesh, 5-15 parts of talc with a particle size of 3000 mesh, and 5-15 parts of heavy calcium with a particle size of 1250 mesh; The film-forming aid comprises the following components in parts by weight: 0.2-0.4 parts of an organosilicon defoamer, 1-2 parts of a wetting and leveling agent, 1-2.5 parts of a dispersant, 2-3.5 parts of a retarder, and 1.5-3 parts of an adhesion promoter; The component A is prepared by the following method: placing a vegetable oil-based modified polyol and a dispersant in a high-speed disperser, mechanically stirring for 5-10 minutes at a speed of 500-700 r / min, then slowly dropping an organosilicon defoamer into the mixture, continuing to stir and mix in the high-speed disperser for 10 minutes, then sequentially adding an antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser, mechanically stirring for 50-90 minutes at a speed of 1200-1500 r / min, the slurry temperature not exceeding 60° C. during the stirring process, then adding a wetting and leveling agent, a retarder, and an adhesion promoter, mechanically stirring for 10-30 minutes at a speed of 500-700 r / min to obtain a crude product, and then filtering the crude product through a 150-mesh gauze and packaging it to obtain component A.

8. The antibacterial solvent-free coating according to claim 7, characterized in that: Comprising component A and component B; The component A comprises the following components in parts by weight: 70 parts of vegetable oil-based modified polyol, 1.5 parts of antibacterial agent, 40 parts of pigment and filler, and 8 parts of film-forming aid; The component B is a silane-modified terminal isocyanate prepolymer; the mass ratio of component A to component B is 2.2:1; The antibacterial agent in the component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; the mass ratio of nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and the intermediate carrier is 3:2:5; the surface porosity of the microsphere is 30%-60%, the particle size D90 of the microsphere is 10-15μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are both 50-80nm, and the pore size of the pores on the surface of the microsphere is 50-100nm; The film-forming aid comprises the following components in parts by weight: 0.3 parts of an organosilicon defoamer, 1.5 parts of a wetting and leveling agent, 1.5 parts of a dispersant, 2.5 parts of a retarder, and 2 parts of an adhesion promoter; The pigments and fillers in component A include the following components in parts by weight: 20 parts of titanium dioxide with a particle size of 800 mesh, 10 parts of talc with a particle size of 3000 mesh, and 10 parts of heavy calcium with a particle size of 1250 mesh.

9. A method for preparing an antibacterial solvent-free coating according to any one of claims 1 to 8, characterized in that: The steps include: A. Synthesis of component A: Place the vegetable oil-based modified polyol and dispersant in a high-speed disperser, stir mechanically for 5-10 minutes at a speed of 500-700 r / min, then slowly drop the organosilicon defoamer into the mixture, continue to stir and mix in the high-speed disperser for 10 minutes, then add the antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser in sequence, stir mechanically for 50-90 minutes at a speed of 1200-1500 r / min, the slurry temperature does not exceed 60°C during the stirring process, then add the wetting and leveling agent, retarder, and adhesion promoter, stir mechanically for 10-30 minutes at a speed of 500-700 r / min to obtain a crude product, and then filter the crude product through a 150-mesh gauze and package it to obtain component A; B. Synthesis of component B: Add the vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stir at 90-120°C for 1-2 h, transfer to a reactor equipped with a vacuum pump, increase the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, keep at 180-220°C for 2-3 h, cool to room temperature, and transfer back to the four-necked flask; then, stir under the protection of dry nitrogen, slowly drop isophorone diisocyanate, organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine into the four-necked flask, raise the temperature to 60 to 90°C after the addition is complete, keep for 2-3 h, then cool to room temperature, and discharge the material to obtain a silane-modified terminal isocyanate prepolymer; C. Component A and component B are uniformly mixed to obtain an antibacterial solvent-free coating.

Citation Information

Patent Citations

  • Compositions, uses and synthetic method of afunctional nanohydroxy apatite and that derivatives

    KR1020060100505A

  • Antimicrobial Devices and Compositions

    US20090035342A1